Comparison and validation of three versions of a forest wind risk model. (June 2015) - Hale, Sophie E.; Gardiner, Barry; Peace, Andrew; Nicoll, Bruce; Taylor, Philip; Pizzirani, Stefania
Abstract: Predicting the probability of wind damage in both natural and managed forests is important for understanding forest ecosystem functioning, the environmental impact of storms and for forest risk management. We undertook a thorough validation of three versions of the hybrid-mechanistic wind risk model, ForestGALES, and a statistical logistic regression model, against observed damage in a Scottish upland conifer forest following a major storm. Statistical analysis demonstrated that increasing tree height and local wind speed during the storm were the main factors associated with increased damage levels. All models provided acceptable discrimination between damaged and undamaged forest stands but there were trade-offs between the accuracy of the mechanistic models and model bias. The two versions of the mechanistic model with the lowest bias gave very comparable overall results at the forest scale and could form part of a decision support system for managing forest wind damage risk. Highlights: Comprehensive description and validation of three versions of a mechanistic wind risk model for even-aged forests. Analysis of the performance of mechanistic and logistic regression models against measured damage in a conifer forest. All models provided acceptable discrimination between damaged and undamaged forest stands. The two version of the mechanistic model with the lowest bias gave very comparable overall results at the forest scale. Statistical analysis showed that increasing tree height and local wind speed were the main factors associated with damage.